Originally Posted by

**jchaney**
If one has only three choices for breakfast combination.

A = Toast

B = Eggs

and B' = Ham

Then we could say that there is a 70% chance of either toast or eggs for breakfast, and 90% chance of toast or ham. Further 30% not toast nor eggs or 10% not toast nor ham. But, what of the those who have toast and eggs, or toast and ham. By this we are saying those had ham are equal to everyone less those who had eggs.

I get P(a) + p(b) - P(anb) = 1 and P(a) + p(b') - P(anb') = 1

but, for p(b)+ p(b') = 1 would not p(anb) + p(a) equal to p(b') and consequently p(a) + p(anb') = p(b)? Where is my logic flawed?

## Bookmarks - Share